2014
DOI: 10.1590/s1677-5538.ibju.2014.04.14
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroneocystostomy in primary vesicoureteral reflux: critical retrospective analysis of factors affecting the postoperative urinary tract infection rates

Abstract: ARTICLE INFO ______________________________________________________________ ______________________Introduction: To determine the parameters affecting the outcome of ureteroneocystostomy (UNC) procedure for vesicoureteral reflux (VUR). Materials and Methods:Data of 398 patients who underwent UNC procedure from 2001 to 2012 were analyzed retrospectively. Different UNC techniques were used according to laterality of reflux and ureteral orifice configuration. Effects of several parameters on outcome were examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
1
4
0
1
Order By: Relevance
“…As the most effective management technique, surgical VUR repair has the highest success rate (>90%) and there is no significant difference with regard to the success rates of the different methods used . In the present study, the success rate of the UNC was 92%, which is in accordance with the rates reported in the literature . The criteria for success in the present study were both radiologic and clinical improvement.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As the most effective management technique, surgical VUR repair has the highest success rate (>90%) and there is no significant difference with regard to the success rates of the different methods used . In the present study, the success rate of the UNC was 92%, which is in accordance with the rates reported in the literature . The criteria for success in the present study were both radiologic and clinical improvement.…”
Section: Discussionsupporting
confidence: 89%
“…In this regard, a Swedish reflux study demonstrated that the most vulnerable to UTI of treated reflux patients were those with LUTD . The data in the literature indicate that the grade and preoperative presence of LUTD do not affect the radiologic success rates for surgical management . However, the rate of clinical improvement is lower in patients with LUTD: the rate of postoperative UTI is higher in LUTD patients, even if the VUR has improved on radiological examination …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ureteroneocystostomy operations has high rate of improvement (92%) [11]. However, this is not the case in case of presence of lower urinary tract pathology.…”
Section: Bilateralmentioning
confidence: 99%
“…The causative risk factors of fUTI after ureteral reimplantation in children with VUR reported thus far were a preoperative grade of reflux, the presence of dysfunctional elimination syndrome, the presence of renal scar and preoperative breakthrough infection, female gender, and voiding dysfunction [7,[9][10][11][12][13]. Nevertheless, the incidence and risk factors of fUTI after ureteral reimplantation in infants have received little attention.…”
mentioning
confidence: 99%